Up (Journal of Parents and Teachers, 2013)
In this section of the magazine the film Up is presented as a tool to deal with a high variety of contents in a cross curricular way. Some of the important contents are the value of elderly people, friendship, love, respect, solidarity, as well as other less transversal contents more specific from some areas, such as, transportation or pets caring. In this section we find a brief summary of the film, activities to do before and after watching it and curiosities related with the film.
Keywords: cross curricular contents; values; activities; film and education